Advanced systems design with Java, UML, and MDA - Lano, K. (Amsterdam ; Boston : Elsevier Butterworth-Heinemann, 2005)
The Model Driven Architecture defines an approach where the specification of the functionality of a system can be separated from its implementation on a particular technology platform. The idea being that the architecture will be able to easily be adapted for different situations, whether they be legacy systems, different languages or yet to be invented platforms. MDA is therefore, a significant evolution of the object-oriented approach to system development. Advanced System Design with Java, UML and MDA describes the factors involved in designing and constructing large systems, illustrating the design process through a series of examples, including a Scrabble player, a jukebox using web streaming, a security system, and others. The book first considers the challenges of software design, before introducing the Unified Modelling Language and Object Constraint Language. The book then moves on to discuss systems design as a whole, covering internet systems design, web services, Flash, XML, XSLT, SOAP, Servlets, Javascript and JSP. In the final section of the book, the concepts and terminology of the Model Driven Architecture are discussed. To get the most from this book, readers will need introductory knowledge of software engineering, programming in Java and basic knowledge of HTML. * Examines issues raised by the Model-Driven Architecture approach to development * Uses easy to grasp case studies to illustrate complex concepts * Focused on the internet applications and technologies that are essential for students in the online age.
Preface; The Challenges of Software Design; UML and OCL; System Design; Internet System Design; Web Services; Model-Driven Architecture; Bibliography; Index.
Includes bibliographical references (p. 323-324) and index.
Keywords: Computer software -- Development; Software architecture; UML (Computer science); Web services -- Design; Internet -- Computer programs -- Design; Services Web -- Conception; Internet -- Logiciels -- Conception; Java (programmeertaal); UML; Electronic books